Breves formas poéticas a lo largo del siglo veinte francés - Casado, Loreto (Anales de Filología Francesa, 2009)
Brevity as artistic expression of modernity personifies the subject of the twentieth century in his/her relation with the time and space. The short form, from Poe and Baudelaire, through Valéry and Surrealism up to contemporary poets themselves, moves away from the aphorism linked to the discourse of a truth and becomes a statement of the subject who questions newforms of thinking and saying. With Rimbaud the features that characterize these «illuminations» are: density, rapidity and the grasp of the moment; that is, a poetic inspired by the haiku and the ideogram which includes a visual and auditory perception as well as an organic thinking which listens to the outer and inner worlds with a minimum of means. This poetry of modernity as writing of the essential, in the most physical sense of the term «writing», challenges the self-absorption of the literary institution at the service of the theoretical abstraction of language.